Methodology for the Study and Analysis of Concrete in a Heritage Façade: The Ateneu Sueco Del Socorro (Spain) - Luis Cortés-Meseguer; Pablo Monzón Bello (Eng)
The Ateneo Sueco del Socorro, built in 1927 in Sueca, Spain, is a prime example of the 20th-century architectural transformation, using reinforced concrete. Designed by architect Juan Guardiola, it reflects the Art Deco style, incorporating ornamental elements from Eastern civilizations. The building’s structure includes masonry walls, concrete columns, and vaulted ceilings. The building displayed a high level of damage due to the oxidation and corrosion of the reinforcements that compose the façade, which led to the definition of the most appropriate study and intervention methodology, applying contemporary tests for reinforced concrete. The original project’s structural design reflects the construction methods of its time, with sculptural elements using Fallas modeling techniques, resulting in various concrete and mortar types. After the façade presented a pathological condition in the early 21st century that made its restoration urgent, a study methodology was followed with current tests to accurately determine the lesions, their degree of damage, and compatible materials for restoration. Corrosion on the façade is mainly triggered by carbonation and the depassivation of reinforcements, exacerbated by environmental issues like moisture retention and oxygen permeability. Repairs should use compatible pre-mixed mortars, with surface inhibitors recommended to extend the lifespan of reinforcements.